Taxonomic review of the “Probetoriformes” species group of Symmachia Hübner, [1819] (Lepidoptera: Riodinidae), with the description of two new species from the Brazilian Atlantic Forest - Dias, Fernando Maia Silva; Dolibaina, Diego Rodrigo; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins (Zootaxa, 2020)
The “Probetoriformes” species group of Symmachia Hübner, [1819] proposed by Stichel (1910; 1930) is redefined based on morphological evidence, and the species herein included in the group are revised. Two new species from the Brazilian Atlantic Forest are described: S. atlantica Dias, Dolibaina & Mielke sp. nov. and S. uirassu Dolibaina, Dias & Casagrande sp. nov. Additionally, one restituted status, S. championi Godman & Salvin, 1886 stat. rest., one revalidated status, S. belti Godman & Salvin, 1886 stat. rev., and one new status, S. meyi Brévignon, 1998 stat. nov., are proposed; therefore, the “Probetoriformes” species group, as herein conceived, includes 10 of the about 60 species of the “catch-all” genus Symmachia. A neotype for Papilio probetor Stoll, 1782 and lectotypes for S. probetor form astiama Seitz, 1913, S. belti and S. championi are designated. The female of the recently described species S. divisora Dolibaina & Leite, 2012 is recognized and described for the first time. Additionally, morphologic illustrations and a dichotomous key for species of the “Probetoriformes” species group are provided.